A review of performance-geared contracting. Issue 2 (15th November 2019) - Odongo, Nickson Herbert; Wang, Daoping; Bishoge, Obadia; Arrive, Tsitaire Jean
Abstract : Purpose: The purpose of this paper is to provide a systematic review of numerous writings addressing quality performance-geared contracting (PC) and self-stated performance. Design/methodology/approach: The study systematically reviewed 134 refereed papers across various fields published between from 2000 to 2018. A categorization framework of PC is suggested addressing fundamental dimensions of its plan and management. Findings: The relative analysis of pertinent articles advancing interdisciplinary perspective encourages learning and provides knowledge about quality management in organizations especially at individual and organizational levels. Research limitations/implications: The outcomes indicate that much of the present-day wide-ranging performance contracting studies do not have robust theoretical grounds. Studies are also inclined to certain theories for instance agency theory and play down other theories with the likelihood of contributing to quality management. Practical implications: Performance contracting between citizens and public entities is important in that the written contract limits what the public entities, for instance, the government can and cannot do and informs on the rights and privileges of citizens, thus contracts to form the core of a free society. Originality/value: This review demonstrates that performance contracting is useful in performance improvement if proper job design and contract management exist.